Mohammad Reza Shajarian's avaz in Iran and beyond, 1979-2010 - Simms, Rob, 1962- (Lexington Books, 2012)
Mohammad Reza Shajarian's Avaz in Iran and Beyond, 1979-2010 is a comprehensive study of the legacy of Mohammad Reza Shajarian, the greatest living exponent of avaz, the traditional art of singing classical Persian poetry. Focusing on Shajarian's career after the Islamic Revolution of 1979, the study includes a detailed examination of the landmark recordings that established him as a national and then global icon of refined Persian culture, artistic excellence, and courageous political resistance.